Understanding patient views and experiences of the IDENTIfication of PALLiative care needs (IDENTI-Pall): a qualitative interview study protocol - Sarah Mitchell; Isabel Leach; Nicola Turner; C R Mayland (BMJ Open)
Introduction More people are living with multimorbidity, defined as two or more long-term physical or mental health conditions. Multimorbidity is associated with poor quality of life and high treatment burden. Palliative care identification tools have been developed for use in primary care to seek out patients who could benefit from a palliative approach to their care. There has been little evaluative research on such tools; patient perspectives on the process of identifying their palliative care needs is a significant gap. The aim of this research is to provide new understanding into patient perspectives of the experience of having their palliative care needs identified, and the impact on their healthcare.Methods and analysis This qualitative study will employ semistructured interviews to elicit the views of participants. We will purposively sample 10–12 adults with advanced serious illness who have been identified by their primary care team as having palliative care needs, and/or are receiving care from specialist palliative care services. A family member or carer may be included in an interview at the participant’s request. A descriptive, thematic analysis will be carried out using the data analysis software NVivo.Ethics and dissemination Ethical approval has been granted by the North of Scotland Research Ethics Committee. Study findings will be disseminated in peer-reviewed journals and through conference presentations. Other activities include the development of patient-centred outcomes for clinical practice and policy in relation to the use of palliative care identification tools.Trial registration number National Institute for Health Research (NIHR) Clinical Studies Portfolio, UK Clinical Research Network (UKCRN) Study number 51296.